2021
DOI: 10.1002/ecs2.3351
|View full text |Cite
|
Sign up to set email alerts
|

Local landscape position impacts demographic rates in a widespread North American steppe bunchgrass

Abstract: Understanding the environmental drivers of demographic rates and population dynamics over space and time is critical for anticipating how species will respond to climate change. While the influence of temporal environmental variation and large environmental gradients are well recognized, less is known about how local topography and landscape position influence demography over small spatial scales. Here, we investigate how local landscape position (north-vs. south-facing aspects) influence the demographic rates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 40 publications
4
18
0
Order By: Relevance
“…This strong interannual seasonal variation in precipitation affects many aspects of plant growth [ 10 , 11 , 19 ]. Due to interannual variation in precipitation, seeds of annual/ephemeral species in the Gurbantunggut Desert, such as Diptychocarpus strictus [ 20 ], Eremopyrum distans [ 9 , 21 ], Erodium oxyrhinchum [ 22 , 23 ], and Isatis violascens [ 24 ], may germinate only in spring or in spring and autumn, depending on when the soil is sufficiently moist for them to do so [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This strong interannual seasonal variation in precipitation affects many aspects of plant growth [ 10 , 11 , 19 ]. Due to interannual variation in precipitation, seeds of annual/ephemeral species in the Gurbantunggut Desert, such as Diptychocarpus strictus [ 20 ], Eremopyrum distans [ 9 , 21 ], Erodium oxyrhinchum [ 22 , 23 ], and Isatis violascens [ 24 ], may germinate only in spring or in spring and autumn, depending on when the soil is sufficiently moist for them to do so [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained by south-facing aspects being more favorable for P. ciliare (Elkind et al 2019; Jarnevich et al 2018). Further, other perennial bunchgrasses in aridlands have been shown to have higher reproductive output on south-facing aspects than on north-facing aspects (Shriver et al 2021). East- and west-facing aspects did not explain P. ciliare distribution in Saguaro National Park; therefore, microclimate differences between east- and west-facing aspects may not have a strong effect on P. ciliare reproduction (Jarnevich et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Abella et al (2012) found that there was no difference in aspect or slope gradient in patches occupied or unoccupied by P. ciliare in Saguaro National Park but concluded that P. ciliare had likely not yet invaded every vulnerable site. Given observed variation in P. ciliare distribution across differing aspects and slope gradients, it is likely that these factors contribute to P. ciliare's ability to establish, grow, and spread, as has been found with other grasses (Shriver et al 2021). However, to date, we are not aware of a study that examines the effects of the abiotic variables of aspect and slope gradient on P. ciliare density, cover, growth, and reproduction at the scale of plant neighborhoods in which plants experience specific microsite conditions and plant-plant interactions are likely to occur (i.e., local scale).…”
Section: Introductionmentioning
confidence: 94%
“…Perennial plants, including grasses, forbs, and shrubs, have declined dramatically in some semiarid rangeland ecosystems over the past century or more, especially where precipitation falls mostly in winter, and these declines have been of great concern to rangeland managers, ranchers, and conservationists. Many of these One of the most striking drivers of variability in the success of plants within some landscapes is aspect ( Armesto and Martinez 1978 ;Nobel and Linton 1997 ;Sternberg and Shoshany 2001 ;Ackerly et al 2002 ;Scherrer and Körner 2010 ;Shriver et al 2021 ). In the Northern Hemisphere, south-facing slopes receive more solar radiation than north-facing slopes and thus are typically the warmest and driest sites on the landscape ( Nobel and Linton 1997 ;Bennie et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the Northern Hemisphere, south-facing slopes receive more solar radiation than north-facing slopes and thus are typically the warmest and driest sites on the landscape ( Nobel and Linton 1997 ;Bennie et al 2008 ). In rangelands of northwestern North America, these south-facing slopes often have lower perennial plant biomass and more invasive annual cover than do north-facing slopes ( Harrison 1999 ;Gelbard and Harrison 2003 ;Shriver et al 2021 ). The lower biomass of perennials may result directly from abiotic effects on the demographic rates of perennials ( Shriver et al 2021 ) but may also be influenced by competition from invasive annuals ( Aguirre and Johnson 1991 ).…”
Section: Introductionmentioning
confidence: 99%